Pengaruh Media Plickers terhadap Motivasi Belajar dan Hasil Belajar Siswa pada Mata Pelajaran PAIBP - Abidah Lailatul Ulwa; Subakri Subakri; Moh. Sutomo (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This research aims to analyze the influence of Plickers media on student motivation and learning outcomes in Islamic Religious Education and Character Education (PAIBP) subjects. This research used an experimental method with a pretest-posttest control group design, involving class VII students at Klabang State Middle School as research subjects. The research results showed that there was a significant increase in student motivation and learning outcomes in the experimental class that used Plickers media. This is proven by the average student posttest score which is higher than the pretest, as well as the Sig. (2-tailed) of 0.00, which indicates a statistically significant difference. Media Plickers provides a learning experience that is interactive, interesting, and motivates students to learn better. These results are consistent with previous research which shows the effectiveness of Plickers media in improving student learning outcomes. This research recommends the use of Plickers media as an innovative learning alternative in improving the quality of education.